High-dielectric-constant polyurethane with side chain containing zwitter-ion pair and preparation and application of high-dielectric-constant polyurethane
By introducing ammonium positive ions/phosphate negative ions and/or phosphate positive ions/sulfonate negative ions as zwitterionic ions pairs in polyurethane, the problems of high OFET operating voltage and defects in inorganic oxide insulation layer are solved, and a high dielectric constant is achieved. Polyurethane dielectric significantly reduces the threshold voltage of the OFET and maintains charge transport performance.
Patent Information
- Application Number
- CN202411502045.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the operating voltage of the OFET is relatively high, and the traditional inorganic oxide insulating layer has problems such as high surface roughness, high temperature processing and poor compatibility, making it difficult to realize a low power consumption and low voltage OFET.
By introducing ammonium positive ions/phosphate negative ions and/or phosphate positive ions/sulfonate negative ions into the polyurethane as zwitterionic pairs, the chain extension method introduces side chain zwitterionic pairs into the polyurethane chain segment, significantly increasing the dielectric constant of the polyurethane. .
It is realized that the capacitance of the dielectric layer is increased and the threshold voltage of the OFET is reduced without reducing the dielectric layer thickness, while avoiding the disadvantages of the inorganic dielectric layer and maintaining the original charge transfer performance.
Smart Images

Figure CN119463099A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectric materials, and in particular relates to a high dielectric constant polyurethane containing a zwitterionic pair in a side chain and a preparation method and application thereof. Background Art
[0002] In recent years, organic field effect transistors (OFETs) have attracted widespread attention due to their ability to carry out various molecular designs and their advantages such as light weight, low manufacturing cost and mechanical flexibility. Although researchers have made a lot of efforts in the development of organic materials for the gate dielectric layer, there are still several problems to be solved, one of which is the high operating voltage. With the continuous development of OFET research and the deepening of understanding, it is found that increasing the capacitance of the dielectric layer is an effective means to achieve low-voltage OFETs. Increasing the capacitance of the dielectric layer can generate more induced charges in the channel, increase the device mobility, and reduce the threshold voltage and operating voltage of the device. Increasing the capacitance can be achieved by reducing the thickness of the dielectric layer or selecting materials with a large dielectric constant. However, reducing the thickness of the dielectric layer will increase the possibility of pinholes penetrating the dielectric layer and destroy the performance of the dielectric layer film. Therefore, the dielectric layer generally uses materials with a large dielectric constant. Traditional inorganic oxide insulating layers can achieve low-power operation of OFETs due to their high dielectric constants, but their shortcomings such as high surface roughness, high-temperature processing, and poor compatibility with organic semiconductors have led to certain limitations in their application. Therefore, developing polymer dielectrics with high dielectric constant is crucial for developing low-voltage and low-energy OFETs.
[0003] As a common type of high molecular polymer, polyurethane has the advantages of excellent mechanical properties, low-temperature processing of solutions, good compatibility with organic semiconductor conjugated molecules, and a wide range of adjustable properties. At the same time, it meets the requirements of high elongation at break and high fatigue resistance for building flexible devices, and is an ideal material for building flexible OFETs. In existing reports, the introduction of ionic groups or ionic components into polyurethane can effectively improve the dielectric constant of polyurethane, but most of the existing reports use direct blending or grafting of ionic liquids or ionic components (such as polyacrylic acid, sodium polybenzenesulfonate, lithium salt and polyethylene glycol composite systems, etc.). The cations and / or anions in this type of system are in a free state, and these ions are easy to aggregate or aggregate into large ion domains. This type of ion aggregate with a large volume or mass cannot switch back and forth under low electric fields or high frequencies, and its dielectric constant will be reduced under high-frequency alternating electric fields.
[0004] Therefore, it is necessary to provide a new high dielectric constant polyurethane containing zwitterionic pairs in the side chain to solve the shortcomings in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a high dielectric constant polyurethane containing a zwitterion pair in the side chain and its preparation and application. The present invention can significantly improve the dielectric constant of polyurethane by introducing ammonium cations / phosphate anions and / or phosphonium cations / sulfonate anions into polyurethane, and when the polyurethane dielectric is applied to OFET as an insulating layer, the threshold voltage can be significantly reduced.
[0006] In the first aspect, the present invention provides a high dielectric constant polyurethane containing a zwitterionic pair in the side chain, which has a structure as shown in formula (I): ; Among them, R 1 Selected from the structures shown in formula (A1)-(A5): , , , , ; R 2 Selected from the structures shown in formula (B1)-(B7): , , , , , , ; R 3 Selected from the structures shown in formula (C1)-(C3): , , ; M is O or NH; m and n are positive integers ≥ 1; x is 1, 2 or 3; R 1 , R 2 , R 3 In Represents the connection location.
[0007] In the present invention, the inventors have found that by introducing zwitterion pairs into the polyurethane chain segments by chain extension means, the positive and negative ions are selected as ammonium cations / phosphate anions and / or phosphonium cations / sulfonate anions, respectively, wherein the zwitterion pairs are all on the side chains. The dielectric constant of the polyurethane can be significantly improved by introducing zwitterion pairs, and the capacitance of the dielectric layer is increased by increasing the dielectric constant without reducing the thickness of the dielectric layer and avoiding pinholes penetrating the dielectric layer to cause damage to the performance of the dielectric layer film. At the same time, the shortcomings of high surface roughness, high temperature processing, and poor compatibility with organic semiconductors of the inorganic dielectric layer are avoided, and zwitterion pairs with larger dipole moments are used to replace ionic liquids or ionic components. The dielectric properties of the polyurethane are improved by introducing zwitterion pairs on the polyurethane side chains, and the zwitterion pairs are switched back and forth at high and low frequencies under the action of an external electric field, so as not to form larger ion aggregations and avoid the reduction of the dielectric constant under high-frequency alternating electric fields; and when the polyurethane dielectric is applied to OFET as an insulating layer, the threshold voltage can be significantly reduced while maintaining the original charge transfer performance.
[0008] In a second aspect, the present invention provides a method for preparing a high dielectric constant polyurethane containing a zwitterion pair in the side chain, comprising the following steps: S1, mixing a polyol, an isocyanate and a catalyst, performing a prepolymerization reaction, and obtaining a polyurethane prepolymer; S2, mixing the polyurethane prepolymer with a first chain extender, performing a primary chain extension reaction, and obtaining a primary chain extension product; S3, mixing the primary chain extension product with a second chain extender, performing a secondary chain extension reaction, and obtaining a secondary chain extension product; S4, mixing the secondary chain extension product with a capping agent, performing a capping reaction, and obtaining a high dielectric constant polyurethane containing a zwitterion pair in the side chain after separation and purification; wherein, in step S2, the first chain extender is a diol small molecule chain extender containing a zwitterion pair in the side chain; and in step S3, the second chain extender is a diol and / or diamine chain extender.
[0009] In the preparation method of the high dielectric constant polyurethane containing zwitterionic pairs in the side chain provided by the present invention, the raw materials are cheap and easily available, the whole preparation process is simple, and it is suitable for large-scale industrial production; at the same time, the polyurethane prepared by the preparation method has a significantly improved dielectric constant.
[0010] In some embodiments, in step S1, the molar ratio of the polyol to the isocyanate is (0.3-0.5):1, for example, it can be 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1 or other ratios within this range; the temperature of the prepolymerization reaction is 50-80°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or other values within this range; the time is 3-5h, for example, it can be 3h, 3.5h, 4h, 4.5h, 5h or other values within this range.
[0011] In some preferred embodiments, the molar ratio of the polymeric polyol to the isocyanate is 0.4:1.
[0012] In some embodiments, the polyol is selected from at least one of polytetramethylene glycol, polyethylene glycol, polypropylene glycol, polycaprolactone glycol, polycarbonate diol, polysiloxane diol, and perfluoropolyether diol; the isocyanate is selected from at least one of isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), and dicyclohexylmethane isocyanate (HMDI).
[0013] In some preferred embodiments, the polyol is polytetrahydrofuran diol, and its molecular weight is 200-10000Da, for example, it can be 200Da, 500Da, 1000Da, 1500Da, 2000Da, 5000Da, 10000Da or other values within this range.
[0014] In some more preferred embodiments, the molecular weight of polytetrahydrofuran diol is 500-2000 Da.
[0015] In some embodiments, in step S1, the catalyst is dibutyltin dilaurate, and the catalyst accounts for 0.2-0.6wt% of the total mass of the polyol, isocyanate, the first chain extender, and the second chain extender, for example, it can be 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt% or other values within this range.
[0016] In some embodiments, in steps S2 and S3, the ratio of the total molar amount of the first chain extender and the second chain extender to the molar amount of isocyanate is (0.5-0.7):1; for example, it can be 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1 or other ratios within this range; the temperature of the first chain extension reaction is 50-80°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or other values within this range; the time is 3-5h, for example, it can be 3h, 3.5h, 4h, 4.5h, 5h or other values within this range; the temperature of the secondary chain extension reaction is room temperature, and the time is 4-6h, for example, it can be 4h, 4.5h, 5h, 5.5h, 6h or other values within this range.
[0017] In some preferred embodiments, the ratio of the total molar amount of the first chain extender and the second chain extender to the molar amount of the isocyanate is 0.6:1.
[0018] It should be noted that the primary chain extension reaction is carried out in the presence of a first organic solvent, and the first organic solvent can be conventionally selected according to actual use needs. For example, in the present invention, the first organic solvent is preferably anhydrous dimethyl sulfoxide. In addition, the amount ratio of the first chain extender to the first organic solvent is preferably 1 mol: (1-10 L), for example, 1 mol: 1 L, 1 mol: 3 L, 1 mol: 5 L, 1 mol: 7 L, 1 mol: 10 L or other ratios within this range.
[0019] The secondary chain extension reaction is carried out in the presence of a second organic solvent, and the second organic solvent can be conventionally selected according to actual use needs. For example, in the present invention, the second organic solvent is preferably anhydrous tetrahydrofuran. In addition, the amount ratio of the first chain extender to the second organic solvent is preferably 1 mol: (0.5-20 L), for example, 1 mol: 0.5 L, 1 mol: 1 L, 1 mol: 5 L, 1 mol: 10 L, 1 mol: 15 L, 1 mol: 20 L or other ratios within this range.
[0020] In some embodiments, the ratio of the first chain extender to the total molar amount of the first chain extender and the second chain extender is 15-95 mol%, for example, it can be 15 mol%, 20 mol%, 25 mol%, 30 mol%, 35 mol%, 40 mol%, 45 mol%, 50 mol%, 55 mol%, 60 mol%, 65 mol%, 70 mol%, 75 mol%, 80 mol%, 85 mol%, 90 mol%, 95 mol% or other values within this range.
[0021] In some embodiments, in steps S2 and S3, the diol small molecule chain extender containing a zwitterion pair on the side chain is selected from at least one of glycerophosphorylcholine, 3-((3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)diphenylphosphonyl)propane-1-sulfonic acid, and 3-((4-(1,3-dihydroxy-2-methylprop-2-yl)phenyl)diphenylphosphonyl)propane-1-sulfonic acid; the diol and / or diamine chain extender is selected from at least one of ethylene glycol, ethylenediamine, butanediol, butanediamine, hexanediol, and hexamethylenediamine.
[0022] In some embodiments, glycerophosphorylcholine (A), 3-((3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)diphenylphosphonyl)propane-1-sulfonic acid (B), 3-((4-(1,3-dihydroxy-2-methylpropan-2-yl)phenyl)diphenylphosphonyl)propane-1-sulfonic acid (C) have the structure shown below:
[0023] In some embodiments, in step S4, the molar ratio of the capping agent to the isocyanate is (0.5-1):1, for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 or other ratios within this range; the temperature of the capping reaction is room temperature, and the time is 1-3h, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h or other values within this range; wherein the capping agent is selected from at least one of anhydrous methanol, anhydrous ethanol, butanol, and ethylene glycol monoethyl ether.
[0024] It should be noted that the polyol and the first chain extender are dried and dehydrated before use. All reactions are carried out under an inert atmosphere, and the present invention does not limit the inert gas, and those skilled in the art can select it according to actual conditions, for example, nitrogen or argon can be preferably used. In addition, after the end-capping reaction is completed, ethyl acetate is used for precipitation 3-5 times and then dissolved in chloroform to form a film.
[0025] In a third aspect, the present invention provides the use of the high dielectric constant polyurethane containing zwitterion pairs in the side chain as described above or the high dielectric constant polyurethane containing zwitterion pairs in the side chain prepared according to any of the above preparation methods in preparing an insulating layer of an organic field effect transistor (OFET) device.
[0026] In some embodiments, the structure of the OFET device includes: a substrate; a gate electrode disposed on the surface of the substrate; an insulating layer disposed on the surface of the substrate and the gate electrode, wherein the material of the insulating layer is a high dielectric constant polyurethane containing zwitterion pairs in the side chain provided by the first aspect of the present invention or prepared by the second aspect; an organic semiconductor layer disposed on the surface of the insulating layer; and a source electrode and a drain electrode disposed on the surface of the organic semiconductor layer.
[0027] In some embodiments, the OFET device structure is a bottom gate top contact; the substrate and gate used are n-type Si wafers or silicon dioxide wafers; the organic semiconductor is conventional commercially available p-type, n-type and bipolar conjugated molecules such as polythiophene, hexaphenyl, polypyrrolopyrrole dione, isoindigo and naphthalene diimide, which are not limited in the present invention; the source electrode and the drain electrode are gold electrodes or silver electrodes; the length of the device channel is 50-200 μm, and the channel width is 500-2000 μm.
[0028] In some embodiments, the OFET device is prepared by the following steps: (1) spin coating the high dielectric constant polyurethane containing zwitterion pairs on the surface of the gate electrode as an insulating layer; (2) forming an organic semiconductor layer on the surface of the insulating layer; (3) evaporating a drain electrode and a source electrode on the surface of the organic semiconductor layer; wherein the concentration of the high dielectric constant polyurethane containing zwitterion pairs on the side chain as the insulating layer solution is 20-30 mg / mL, and the concentration of the organic semiconductor is 5-10 mg / mL; during the evaporation process, the vacuum degree is below 10-4 Pa.
[0029] The beneficial effect of the present invention is that, different from the prior art, the present invention introduces zwitterion pairs into the polyurethane chain segments by chain extension, wherein the positive and negative ions are selected as ammonium positive ions / phosphate negative ions and / or phosphonium positive ions / sulfonate negative ions, respectively, wherein the zwitterion pairs are both on the side chains. The dielectric constant of the polyurethane can be significantly improved by introducing the zwitterion pairs, and further, when the polyurethane dielectric is applied to an OFET as an insulating layer, the threshold voltage can be significantly reduced while maintaining the original charge transfer performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a hydrogen nuclear magnetic resonance spectrum of the high dielectric constant polyurethane containing zwitterion pairs in the side chains prepared in Example 3 of the present invention; Figure 2 The dielectric constant diagram of high dielectric constant polyurethanes containing zwitterion pairs in different side chains prepared in Comparative Example 1 and Examples 1-5, 8, and 13 of the present invention; Figure 3 Graphs showing Young's modulus and elongation at break of high dielectric constant polyurethanes containing zwitterion pairs in different side chains prepared in Comparative Example 1 and Examples 1-5, 8, and 13 of the present invention; Figure 4 It is a schematic structural diagram of an organic field effect transistor (OFET) device in the present invention; The reference numerals have the following meanings: 1: substrate, 2: gate electrode, 3: insulating layer, 4: organic semiconductor layer, 5: source electrode, and 6: drain electrode. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.
[0033] Example 1 Take polytetrahydrofuran diol (PTMG, Mn = 1000 Da, 0.01 mol) was placed in a 250 mL three-necked flask, vacuum dried at 120 ° C for 2 h, and then cooled to 75 ° C under argon protection, and dicyclohexylmethane diisocyanate (HMDI, 0.025 mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4 h, and the system became viscous; glycerol phosphorylcholine (0.0025 mol) was placed in a 50 mL single-necked flask, vacuum dried at 75 ° C for 2 h, and then the solid was added to the reaction system. After 30 min, 20 ml of anhydrous dimethyl sulfoxide was added and reacted at 75 ° C for 4 h. The reaction system was cooled to room temperature, and ethylenediamine (0.0125 mol) was taken and added to the reaction system in small amounts for multiple times. With the addition of ethylenediamine, the viscosity of the system increased rapidly, and it was diluted with 50 mL of anhydrous tetrahydrofuran. After reacting for 4 h, anhydrous methanol (0.0125 mol) was added to cap the reaction for 2 h to stop the reaction. The reaction mixture was precipitated with ethyl acetate three times, and the insoluble matter was dissolved with chloroform to form a film.
[0034] Example 2 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask and dried under vacuum at 120°C for 2h. Then, the temperature was lowered to 75°C under argon protection. Dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added and reacted for 4h. The system became viscous. Glycerylphosphorylcholine (0.005mol) was placed in a 50mL three-necked flask and dried under vacuum at 120°C for 2h. L single-mouth flask, vacuum dried at 75℃ for 2h, then added the solid to the reaction system, added 20ml anhydrous dimethyl sulfoxide after 30min, reacted at 75℃ for 4h, cooled the reaction system to room temperature, took ethylenediamine (0.01mol) and added it to the reaction system in small amounts several times, with the addition of ethylenediamine, the viscosity of the system increased rapidly, diluted with 40mL anhydrous tetrahydrofuran, reacted for 4h, added anhydrous methanol (0.0125mol) to cap the reaction for 2h to stop the reaction. Use ethyl acetate to precipitate 3 times, and dissolve the insoluble matter with chloroform to form a film.
[0035] Example 3 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask and dried under vacuum at 120°C for 2h. Then, the temperature was lowered to 75°C under argon protection. Dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added and reacted for 4h. The system became viscous. Glycerylphosphorylcholine (0.0075mol) was placed in a 50mL three-necked flask and dried under vacuum at 120°C for 2h. L single-mouth flask, vacuum dried at 75℃ for 2h, then added the solid to the reaction system, added 20ml of anhydrous dimethyl sulfoxide after 30min, reacted at 75℃ for 4h, cooled the reaction system to room temperature, took ethylenediamine (0.0075mol) and added it to the reaction system in small amounts and multiple times, with the addition of ethylenediamine, the viscosity of the system increased rapidly, diluted with 30mL of anhydrous tetrahydrofuran, reacted for 4h, added anhydrous methanol (0.0125mol) to cap the reaction for 2h to stop the reaction. Use ethyl acetate to precipitate 3 times, and dissolve the insoluble matter with chloroform to form a film.
[0036] Example 4 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask and dried under vacuum at 120°C for 2h. Then, the temperature was lowered to 75°C under argon protection. Dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added and reacted for 4h. The system became viscous. Glycerylphosphorylcholine (0.01mol) was placed in a 50mL A single-mouth flask was vacuum dried at 75°C for 2 hours, and then the solid was added to the reaction system. After 30 minutes, 20 ml of anhydrous dimethyl sulfoxide was added, and the reaction was carried out at 75°C for 4 hours. The reaction system was cooled to room temperature, and ethylenediamine (0.005 mol) was added to the reaction system in small amounts and multiple times. With the addition of ethylenediamine, the viscosity of the system increased rapidly. It was diluted with 20 mL of anhydrous tetrahydrofuran, and after 4 hours of reaction, anhydrous methanol (0.0125 mol) was added to cap the reaction for 2 hours to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved with chloroform to form a film.
[0037] Example 5 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask and dried under vacuum at 120°C for 2h. Then, the temperature was lowered to 75°C under argon protection. Dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added and reacted for 4h. The system became viscous. Glycerylphosphorylcholine (0.0125mol) was placed in a 100mL three-necked flask and dried under vacuum at 120°C for 2h. L single-mouth flask, vacuum dried at 75℃ for 2h, then added the solid to the reaction system, added 20ml of anhydrous dimethyl sulfoxide after 30min, reacted at 75℃ for 4h, cooled the reaction system to room temperature, took ethylenediamine (0.0025mol) and added it to the reaction system in small amounts and multiple times. With the addition of ethylenediamine, the viscosity of the system increased rapidly, diluted with 10mL of anhydrous tetrahydrofuran, reacted for 4h, and then added anhydrous methanol (0.0125mol) to cap the reaction for 2h to stop the reaction. Use ethyl acetate to precipitate 3 times, and dissolve the insoluble matter with chloroform to form a film.
[0038] Example 6 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask, vacuum dried at 120℃ for 2h, then cooled to 75℃ under argon protection, and dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h, and the system became viscous; 3-((3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)diphenylphosphonyl)propane-1-sulfonic acid (0.0025mol) in a 50mL single-necked flask, vacuum dried at 75℃ for 2h, then added the solid to the reaction system, added 20ml of anhydrous dimethyl sulfoxide after 30min, reacted at 75℃ for 4h, cooled the reaction system to room temperature, added ethylenediamine (0.0125mol) in small amounts and added to the reaction system several times, with the addition of ethylenediamine, the viscosity of the system increased rapidly, diluted with 50mL of anhydrous tetrahydrofuran, reacted for 4h, added anhydrous methanol (0.0125mol) to cap the reaction for 2h to stop the reaction. Use ethyl acetate to precipitate 3 times, and dissolve the insoluble matter with chloroform to form a film.
[0039] Example 7 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask and dried under vacuum at 120°C for 2h. Then, the temperature was lowered to 75°C under argon protection. Dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h. The system became viscous. 3-((3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)diphenylphosphonyl)propane-1-sulfonic acid was added to Acid (0.005 mol) was placed in a 50 mL single-necked flask, vacuum dried at 75 ° C for 2 hours, and then the solid was added to the reaction system. After 30 minutes, 20 ml of anhydrous dimethyl sulfoxide was added, and the reaction was carried out at 75 ° C for 4 hours. The reaction system was cooled to room temperature, and ethylenediamine (0.01 mol) was added to the reaction system in small amounts and multiple times. With the addition of ethylenediamine, the viscosity of the system increased rapidly. It was diluted with 40 mL of anhydrous tetrahydrofuran. After the reaction was carried out for 4 hours, anhydrous methanol (0.0125 mol) was added to cap the reaction for 2 hours to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved with chloroform to form a film.
[0040] Example 8 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask, vacuum dried at 120℃ for 2h, then cooled to 75℃ under argon protection, and dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h, and the system became viscous; 3-((3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)diphenylphosphonyl)propane-1-sulfonic acid (0.0075mol) in a 50mL single-necked flask, vacuum dried at 75℃ for 2h, then added the solid to the reaction system, added 20ml of anhydrous dimethyl sulfoxide after 30min, reacted at 75℃ for 4h, cooled the reaction system to room temperature, added ethylenediamine (0.0075mol) in small amounts and added to the reaction system several times, with the addition of ethylenediamine, the viscosity of the system increased rapidly, diluted with 30mL of anhydrous tetrahydrofuran, reacted for 4h, added anhydrous methanol (0.0125mol) to cap the reaction for 2h to stop the reaction. Use ethyl acetate to precipitate 3 times, and dissolve the insoluble matter with chloroform to form a film.
[0041] Example 9 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask and dried under vacuum at 120°C for 2h. Then, the temperature was lowered to 75°C under argon protection. Dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h. The system became viscous. 3-((3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)diphenylphosphonyl)propane-1-sulfonic acid was added to Acid (0.01 mol) was placed in a 50 mL single-necked flask, vacuum dried at 75 ° C for 2 hours, and then the solid was added to the reaction system. After 30 minutes, 20 ml of anhydrous dimethyl sulfoxide was added, and the reaction was carried out at 75 ° C for 4 hours. The reaction system was cooled to room temperature, and ethylenediamine (0.005 mol) was added to the reaction system in small amounts and multiple times. With the addition of ethylenediamine, the viscosity of the system increased rapidly. It was diluted with 20 mL of anhydrous tetrahydrofuran. After the reaction was carried out for 4 hours, anhydrous methanol (0.0125 mol) was added to cap the reaction for 2 hours to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved with chloroform to form a film.
[0042] Example 10 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask, dried under vacuum at 120℃ for 2h, then cooled to 75℃ under argon protection, and dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h, and the system became viscous; 3-((3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)diphenylphosphonyl)propane-1-sulfonic acid ( 0.0125mol) in a 100mL single-necked flask, vacuum dried at 75℃ for 2h, then added the solid to the reaction system, 20ml of anhydrous dimethyl sulfoxide was added after 30min, and the reaction was carried out at 75℃ for 4h, then the reaction system was cooled to room temperature, ethylenediamine (0.0025mol) was taken and added to the reaction system in small amounts and multiple times, with the addition of ethylenediamine, the viscosity of the system increased rapidly, and it was diluted with 10mL of anhydrous tetrahydrofuran, and after the reaction for 4h, anhydrous methanol (0.0125mol) was added to cap the reaction for 2h to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved with chloroform to form a film.
[0043] Embodiment 11 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask, vacuum dried at 120℃ for 2h, then cooled to 75℃ under argon protection, and dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h, and the system became viscous; 3-((4-(1,3-dihydroxy-2-methylprop-2-yl)phenyl)diphenylphosphonyl)propane-1- Sulfonic acid (0.0025 mol) was placed in a 50 mL single-necked flask and dried under vacuum at 75 °C for 2 h. The solid was added to the reaction system. After 30 min, 20 ml of anhydrous dimethyl sulfoxide was added. The reaction was continued at 75 °C for 4 h. The reaction system was cooled to room temperature. Ethylene diamine (0.0125 mol) was added to the reaction system in small amounts and multiple times. With the addition of ethylene diamine, the viscosity of the system increased rapidly. The reaction was diluted with 50 mL of anhydrous tetrahydrofuran. After 4 h of reaction, anhydrous methanol (0.0125 mol) was added to terminate the reaction for 2 h to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved with chloroform to form a film.
[0044] Example 12 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask and dried under vacuum at 120℃ for 2h. Then, the temperature was lowered to 75℃ under argon protection. Dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h. The system became viscous. 3-((4-(1,3-dihydroxy-2-methylprop-2-yl)phenyl)diphenylphosphonyl)propane-1 -sulfonic acid (0.005 mol) in a 50 mL single-necked flask, vacuum dried at 75 ° C for 2 hours, then added to the reaction system, 20 ml of anhydrous dimethyl sulfoxide was added after 30 minutes, and the reaction was carried out at 75 ° C for 4 hours. The reaction system was cooled to room temperature, ethylenediamine (0.01 mol) was taken and added to the reaction system in small amounts and multiple times. With the addition of ethylenediamine, the viscosity of the system increased rapidly, and it was diluted with 40 mL of anhydrous tetrahydrofuran. After the reaction was carried out for 4 hours, anhydrous methanol (0.0125 mol) was added to cap the reaction for 2 hours to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved with chloroform to form a film.
[0045] Embodiment 13 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask, vacuum dried at 120℃ for 2h, then cooled to 75℃ under argon protection, and dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h, and the system became viscous; 3-((4-(1,3-dihydroxy-2-methylprop-2-yl)phenyl)diphenylphosphonyl)propane-1- Sulfonic acid (0.0075 mol) was placed in a 50 mL single-necked flask and dried under vacuum at 75 °C for 2 h. The solid was added to the reaction system. After 30 min, 20 ml of anhydrous dimethyl sulfoxide was added. The reaction was continued at 75 °C for 4 h. The reaction system was cooled to room temperature. Ethylene diamine (0.0075 mol) was added to the reaction system in small amounts and multiple times. With the addition of ethylene diamine, the viscosity of the system increased rapidly. The reaction was diluted with 30 mL of anhydrous tetrahydrofuran. After 4 h of reaction, anhydrous methanol (0.0125 mol) was added to cap the reaction for 2 h to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved with chloroform to form a film.
[0046] Embodiment 14 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask and dried under vacuum at 120℃ for 2h. Then, the temperature was lowered to 75℃ under argon protection. Dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h. The system became viscous. 3-((4-(1,3-dihydroxy-2-methylprop-2-yl)phenyl)diphenylphosphonyl)propane-1 -sulfonic acid (0.01 mol) in a 50 mL single-necked flask, vacuum dried at 75 ° C for 2 hours, then the solid was added to the reaction system, 20 ml of anhydrous dimethyl sulfoxide was added after 30 minutes, and the reaction was carried out at 75 ° C for 4 hours, and the reaction system was cooled to room temperature, and ethylenediamine (0.005 mol) was added to the reaction system in small amounts and multiple times. With the addition of ethylenediamine, the viscosity of the system increased rapidly, and it was diluted with 20 mL of anhydrous tetrahydrofuran. After the reaction was carried out for 4 hours, anhydrous methanol (0.0125 mol) was added to cap the reaction for 2 hours to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved in chloroform to form a film.
[0047] Embodiment 15 Polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) was placed in a 250mL three-necked flask, vacuum dried at 120℃ for 2h, then cooled to 75℃ under argon protection, and dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) were added to react for 4h, and the system became viscous; 3-((4-(1,3-dihydroxy-2-methylprop-2-yl)phenyl)diphenylphosphonyl)propane-1-sulfonic acid was added to react with 1% 3-((4-(1,3-dihydroxy-2-methylprop-2-yl)phenyl)diphenylphosphonyl)propane-1-sulfonic acid Acid (0.0125mol) was placed in a 100mL single-necked flask, vacuum dried at 75℃ for 2h, and then the solid was added to the reaction system. After 30min, 20ml of anhydrous dimethyl sulfoxide was added, and the reaction was continued at 75℃ for 4h. The reaction system was cooled to room temperature, and ethylenediamine (0.0025mol) was added to the reaction system in small amounts and multiple times. With the addition of ethylenediamine, the viscosity of the system increased rapidly. It was diluted with 10mL of anhydrous tetrahydrofuran, and after 4h of reaction, anhydrous methanol (0.0125mol) was added to cap the reaction for 2h to stop the reaction. Ethyl acetate was used for precipitation 3 times, and the insoluble matter was dissolved with chloroform to form a film.
[0048] Comparative Example 1 Take polytetrahydrofuran diol (PTMG, Mn = 1000Da, 0.01mol) in a 250mL three-necked bottle, vacuum dry at 120℃ for 2h, cool to 75℃ under argon protection, add dicyclohexylmethane diisocyanate (HMDI, 0.025mol) and catalyst dibutyltin dilaurate (DBTDL, 0.4wt%) to react for 4h, the system becomes viscous; cool the reaction system to room temperature, take ethylenediamine (0.015mol) and add it to the reaction system in small amounts and multiple times. With the addition of ethylenediamine, the viscosity of the system increases rapidly, dilute with 70mL anhydrous chloroform: anhydrous N,N-dimethylformamide = 1:1, react for 4h, add anhydrous methanol (0.0125mol) to cap the reaction for 2h to stop the reaction. Use ethyl acetate to precipitate 3 times, and dissolve the insoluble matter with methanol: chloroform = 1:1 to form a film.
[0049] Performance Testing The high dielectric constant polyurethanes obtained by polymerization of PTMG-1000 and HMDI with diol small molecule chain extenders containing zwitterionic pairs in different side chains and ethylenediamine in the above comparative example 1 and examples 1-5, 8, and 13 were characterized as follows: Nuclear magnetic resonance hydrogen spectrum test: The high dielectric constant polyurethane film was tested using a nuclear magnetic resonance spectrometer (NMR400MHz).
[0050] Dielectric constant test: The dielectric constant of the high dielectric constant polyurethane film was tested using a dielectric constant analyzer (ZJD-E) at a temperature of 22°C, a humidity of 60%, a measurement frequency of 102-106 Hz, and three tests. The data error was within 10%.
[0051] For example, the nuclear magnetic resonance hydrogen spectrum of the high dielectric constant polyurethane containing zwitterionic pairs in the side chain prepared in Example 3 is as follows: Figure 1 shown.
[0052] from Figure 1 It can be seen that the peak at the chemical shift of 3.31ppm is the calibration peak of methanol; the peak at the chemical shift of about 3.54ppm is attributed to the proton on the HMDI methylene at the α position next to the N in the carbamate bond, and the peak at the chemical shift of about 1.72 is attributed to the protons on other methylene groups of HMDI, the protons on the β position methylene on PTMG connected to the carbamate bond, and the protons on the β position of the phosphate anion, both of which contain repeating units, so the integrated area is large; the peak at the chemical shift of 5.09ppm corresponds to the proton of the carbon at the α position next to the oxygen of the chain extender connected to the carbamate bond, and the peak at the chemical shift of 3.85ppm corresponds to the proton on the α position methylene on PTMG connected to the carbamate, and the integrated areas of the two meet the feed ratio. These evidences indicate the successful introduction of the chain extender.
[0053] The dielectric constant, Young's modulus and elongation at break of the high dielectric constant polyurethane containing zwitterion pairs in the side chain prepared in Comparative Example 1 and Examples 1-5, 8 and 13 are as follows: Figure 2 , 3 shown.
[0054] from Figure 2 It can be seen that compared with the comparative example, the dielectric constant of the polyurethane prepared in the embodiment of the present invention is significantly increased, and as the content of the added chain extender increases, the dielectric constant also increases accordingly. The results show that in the present invention, by introducing zwitterion pairs into the polyurethane, the dielectric constant of the polyurethane can be significantly increased.
[0055] from Figure 3 It can be seen that compared with the comparative example, the Young's modulus of the polyurethane prepared in the embodiment of the present invention decreases and the elongation at break increases. The results show that the polyurethane prepared in the present invention has better performance.
[0056] Application Testing The high dielectric constant polyurethane containing zwitterion pairs in the side chains prepared in Comparative Example 1 and Examples 1-5, 8, and 13 of the present invention was used as an insulating layer to prepare OFETs. Figure 4, which is a schematic diagram of the structure of the OFET device in the present invention. Specifically, the structure of the OFET device includes: a substrate 1; a gate electrode 2 arranged on the surface of the substrate 1; an insulating layer 3 arranged on the surface of the gate electrode 2, and the material of the insulating layer 3 is a high dielectric constant polyurethane with a zwitterion pair in the side chain provided by the present invention; an organic semiconductor layer 4 arranged on the surface of the insulating layer 3; a source electrode 5 and a drain electrode 6 arranged on the surface of the organic semiconductor 4.
[0057] The preparation method of the OFET comprises the following steps: 1) SiO 2 The sheet was placed in a mixed solution of hydrogen peroxide and concentrated sulfuric acid in a volume ratio of 3:7, heated at 150°C for 90 minutes, and after cooling, the surface was rinsed with deionized water and acetone in turn, and then blown dry with a nitrogen gun for later use; a UV-ozone cleaning machine was used to irradiate ozone for about 10-20 minutes to further clean the SiO 2 Organic matter on the surface of the film; 2) Use a coating machine to coat SiO 2 Different types of polyurethane were spin-coated on the surface of the film. The concentration of the polyurethane solution was 20 mg / mL (the solvent was a mixture of methanol and chloroform in a volume ratio of 1:1). It was filtered three times with a polytetrafluoroethylene ultrafiltration membrane with a pore size of 0.45 μm. The spin-coating speed was 3200 rpm / min and the spin-coating time was 50 s. A uniform polyurethane film with a film thickness of 100 nm was obtained. After vacuum annealing at 180°C, an organic semiconductor with a concentration of 5 mg / mL (dissolved in chloroform) was spin-coated. It was filtered three times with a polytetrafluoroethylene ultrafiltration membrane with a pore size of 0.45 μm. The spin-coating speed was 3000 rpm / min and the spin-coating time was 40 s. The thickness of the semiconductor polymer film was 50 nm. Among them, the organic semiconductor is polypyrrolopyrrole diketo-terthiophene (DPP-TTT), and the specific structural formula is as follows:
[0058] 3) Transfer the substrate to the metal electrode evaporation equipment and place it in a vacuum of 10 -4 Under Pa, 50nm Au source electrode and drain electrode were evaporated using a stencil to obtain a device with a bottom-gate top-contact configuration. The length of the device channel was 100μm and the width was 1000μm.
[0059] The devices prepared above were tested using Keithley 4200SCS semiconductor performance tester, and the output characteristic curve and transfer characteristic curve were measured by this instrument, thereby obtaining data characterizing OFET such as carrier mobility, current switching ratio and threshold voltage.
[0060] Among them, the current switching ratio is the ratio of the source-drain current ISD when the device is in the "on" and "off" states; Among them, the carrier mobility can be calculated by the formula (through |ID| 1 / 2 With V G The slope of the fitted curve can be used to calculate the mobility); (where μ is carrier mobility, L / W is the aspect ratio of the device channel, C i is the area capacitance of the high dielectric constant polyurethane insulation layer); Among them, for |ID| 1 / 2 With V G The relationship curve is fitted, and the fitting line is V G The intersection of the axes is the threshold voltage V of the transistor. th .
[0061] The obtained data are shown in Table 1 below.
[0062] Table 1 Performance test results of OFET
[0063] As can be seen from Table 1, increasing the content of diol small molecule chain extender with zwitterions in the side chain will lead to a sharp drop in the threshold voltage, while significantly increasing the carrier mobility of the device; after a certain content, continuing to increase the content of diol small molecule chain extender with zwitterions has little effect on the threshold voltage, and does not form a regular change relationship with the dielectric constant. The above data can show that polyurethane films containing zwitterionic side chains can be used as dielectric layers of OFET devices to obtain devices with relatively excellent performance, and have great application potential.
[0064] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0065] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high dielectric constant polyurethane containing zwitterionic pairs in the side chains, characterized in that: It has a structure as shown in formula (I): ; Wherein, R1 is selected from the structures shown in formula (A1)-(A5): 、 、 、 、 ; R2 is selected from the structures shown in formula (B1)-(B7): 、 、 、 、 、 、 ; R3 is selected from the structures shown in formula (C1)-(C3): 、 、 ; M is O or NH; m and n are positive integers ≥ 1; x is 1, 2 or 3; R1, R2, R3 Represents the connection location.
2. A method for preparing a high dielectric constant polyurethane containing a zwitterionic pair in the side chain, characterized in that: The steps include: S1, mixing polyol, isocyanate and catalyst, and performing prepolymerization to obtain polyurethane prepolymer; S2, mixing the polyurethane prepolymer with the first chain extender, performing a primary chain extension reaction, and obtaining a primary chain extension product; S3, mixing the primary chain extension product with a second chain extender to perform a secondary chain extension reaction to obtain a secondary chain extension product; S4, mixing the secondary chain extension product with a capping agent, performing a capping reaction, and obtaining a high dielectric constant polyurethane containing a zwitterion pair in the side chain after separation and purification; Wherein, in step S2, the first chain extender is a diol small molecule chain extender having a zwitterion pair in the side chain; in step S3, the second chain extender is a diol and / or diamine chain extender.
3. The preparation method according to claim 2, characterized in that: In step S1, the molar ratio of the polyol to the isocyanate is (0.3-0.5):1, the temperature of the prepolymerization reaction is 50-80°C, and the time is 3-5h.
4. The preparation method according to claim 3, characterized in that: The polyol is selected from at least one of polytetramethylene glycol, polyethylene glycol, polypropylene glycol, polycaprolactone glycol, polycarbonate glycol, polysiloxane glycol and perfluoropolyether glycol; The isocyanate is selected from at least one of isophorone diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate and dicyclohexylmethane isocyanate.
5. The preparation method according to claim 2, characterized in that: In step S1, the catalyst is dibutyltin dilaurate, and the catalyst accounts for 0.2-0.6wt% of the total mass of the polyol, isocyanate, the first chain extender and the second chain extender.
6. The preparation method according to claim 2, characterized in that: In steps S2 and S3, the ratio of the total molar amount of the first chain extender and the second chain extender to the molar amount of the isocyanate is (0.5-0.7):1; The temperature of the first chain extension reaction is 50-80°C and the time is 3-5h; The temperature of the secondary chain extension reaction is room temperature and the time is 4-6 hours.
7. The preparation method according to claim 6, characterized in that: The ratio of the first chain extender to the total molar amount of the first chain extender and the second chain extender is 15-95 mol%.
8. The preparation method according to claim 2, characterized in that: In steps S2 and S3, the diol small molecule chain extender containing a zwitterion pair on the side chain is selected from at least one of glycerophosphorylcholine, 3-((3-hydroxy-2-(hydroxymethyl)-2-methylpropyl)diphenylphosphonyl)propane-1-sulfonic acid, and 3-((4-(1,3-dihydroxy-2-methylprop-2-yl)phenyl)diphenylphosphonyl)propane-1-sulfonic acid; The diol and / or diamine chain extender is at least one selected from ethylene glycol, ethylenediamine, butanediol, butanediamine, hexanediol, and hexamethylenediamine.
9. The preparation method according to claim 2, characterized in that: In step S4, the molar ratio of the blocking agent to the isocyanate is (0.5-1):1, the blocking reaction temperature is room temperature, and the time is 1-3 hours; Wherein, the end-capping agent is selected from at least one of anhydrous methanol, anhydrous ethanol, butanol, and ethylene glycol monoethyl ether.
10. Use of the high dielectric constant polyurethane containing zwitterion pairs in the side chains according to claim 1 or the high dielectric constant polyurethane containing zwitterion pairs in the side chains prepared by the preparation method according to any one of claims 2 to 9 in preparing the insulating layer of an organic field effect transistor device.